Introduction to the Revised Bakery Science Lab Manuals - Shearon, Chloe C. (My University, 2017)
I chose to revise the Bakery Science I and II lab manuals because I saw an unfulfilled need in the Grain Science Department. I had tossed around the idea of doing a research project, speaking with Dave Krishock and Dr. Becky Miller to explore opportunities and gather ideas, but after taking Bakery Science I and II, I realized I could use my writing skills to streamline the courses and to help future students.